Curating street art - Abarca, Javier (SAUC - Street Art and Urban Creativity (repository), 2017)
After being largely ignored for decades, street art has in the last ten years been increasingly assimilated by society and the art system. Numerous artists who started their careers producing street work on their own initiative and without seeking permission are now being commissioned to create official public art – mostly murals – and pieces for galleries, museums and collections. This paper looks at the differences between producing art in public space without permission and producing art for the gallery, and at the possible approaches to the commission of gallery artworks related to the street practice of an artist. It ends with an analysis of the problems and possibilities of commissioning pieces to be produced in the street without permission.